Dukungan Keluarga dan Kualitas Hidup Pasien Kanker - Vina Noviani; Edwina Rugaiah Monayo; Sri Yulian Hunowu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the family support and quality of life of cancer patients at the Surgical Oncology Specialist Clinic in Gorontalo City. The method used in this study was quantitative with a descriptive design. The results showed that the majority of respondents received high levels of family support (43 respondents (89.6%). Quality of life on the functional scale was mostly in the good category (37 respondents (77.1%), quality of life on the symptom scale was mostly in the mild category (33 respondents (68.8%), and quality of life on the global scale was mostly in the good category (25 respondents (52.1%). In conclusion, cancer patients at the Surgical Oncology Specialist Clinic in Gorontalo City generally have high levels of family support and a relatively good quality of life. Optimal family support needs to be maintained to improve patient well-being during treatment. Keywords: Family Support, Quality of Life, Cancer Patients